Fat and Wingless signaling oppositely regulate epithelial cell-cell adhesion and distal wing development in Drosophila. - Jaiswal, M.; Agrawal, N.; Sinha, P. (Development, 2006)
Development of organ-specific size and shape demands tight coordination between tissue growth and cell-cell adhesion. Dynamic regulation of cell adhesion proteins thus plays an important role during organogenesis. In Drosophila, the homophilic cell adhesion protein DE-Cadherin (DE-Cad) regulates epithelial cell-cell adhesion at adherens junctions (AJs). Here, we show that along the proximodistal (PD) axis of the developing wing epithelium, apical cell shapes and expression of DE-Cad are graded in response to Wingless (Wg), a morphogen secreted from the dorsoventral (DV) organizer in distal wing, suggesting a PD gradient of cell-cell adhesion. The Fat (Ft) tumor suppressor, by contrast, represses DE-Cad expression. In genetic tests, ft behaves as a suppressor of Wg signaling. Cytoplasmic pool of beta-catenin/Arm, the intracellular transducer of Wg signaling, is negatively correlated with the activity of Ft. Moreover, unlike that of Wg, signaling by Ft negatively regulates the expression of Distalless (Dll) and Vestigial (Vg). Finally, we show that Ft intersects Wnt/Wg signaling, downstream of the Wg ligand. Fat and Wg signaling thus exert opposing regulation to coordinate cell-cell adhesion and patterning along the PD axis of Drosophila wing.